Travel risk perception and travel experience as factors influencing travel decision among the international tourists to Penang, Malaysia - Zainol, Noor Azimin; Mohd Shariff, Nurhazani (Universiti Utara Malaysia Press, 2007)
Safety and security have been a major issue and plays an important role in the travel industry.Travel risk perceptions and past travel experience have undoubtedly been proven to be among major factors contributing to future travel decision.The purpose of this study was to review the travel risk perception and past travel experience as factors influencing travel decisions among the international tourists to Penang, Malaysia.This study had reviewed the literatures being done on travel risk perception and past travel experience that has influenced on future travel decisions.Questionnaire surveys were distributed to 200 international tourists in Penang and a chi-square x2 test was done to determine whether travel risk perception and past travel experience has influenced travel decisions made by the respondents.Other classification variables besides the hyphotheses were analyzed using the SPSS for descriptive statistics measures (max, min, mean, frequency and percentage).It was found that travel risk perceptions and past travel experience among the international tourists are not factors influencing their travel decision to Penang.As safety and security is a major concern, this paper can bring benefit by identifying the risks and destination countries can design ways to reduce the risks and find alternatives to prevent or overcome the negative consequences.